COMPARATIVE ADVANTAGE METRICS OF ROMANIA’S EXPORTS IN THE PERIOD 2007-2010 - Gheorghe ZAMAN; Valentina Vasile (Revista Romana de Economie, 2012)
The research work consists of two parts. In the first theoretical part we analyse the formulae of revealed comparative advantages (RCA) and of the Grubel-Lloyd indices as an analysis instrument of international specialisation and of inter- and intra-industry one of national economies. The second part analytically presents the outcomes of computing the two indicators in the case of the Romanian economy in the post-accession period 2007-2010 by making use of the Eurostat database for intra and extra EU-27 trade by the nine SITC (Standard International Trade Classification) Rev. 4 categories.